Bowman Layer Transplantation—A Review. Issue 6 (November 2020) - Parker, Jack S.; Dockery, Philip W.; Melles, Gerrit R.J.
Abstract : Abstract: Bowman layer (BL) transplantation has been described for various indications, including the treatment of postrefractive corneal haze, postherpetic scarring, and keratoconus. The unique properties of the BL explain its versatility. Robust, thin, and acellular, transplanted BL inhibits stromal scarring, flattens ectatic corneas, and poses minimal risk of immune reaction. This article reviews the history of BL transplantation and recent developments, and anticipated next steps for the procedure.